A study of filamentous fungi in bottled drinking water sold in Tacloban City - Lacdo-o, Christine G. (2016)
Waterborne fungi have been associated with odour and foul taste in drinking water. Fungi have been reported from all types of water, from raw water to treated water, and from heavily polluted water to distilled or ultra-purewater. Accounted for contaminating water, fungi have the ability to survive after filtration. Bottled drinking water produced by commercial brands was evaluated in this study. Two methods of fungal isolation were utilized, namely: membrane filtration technique and spread plate technique. The isolated specimens were grown on potato dextrose agar and were identified through slide-culture technique. Twenty species of fungi were detected. These species belong to six different genera, namely, Acremonium, Aspergillus, Botrytis, Cylindrocarpon, Neosartorya and Penicillium. All these genera have species which are harmful to man. The most abundant species is Aspergillus. There were more fungi present in Brand A.